The Students’ Preference on Using TOEFL Applications for Grammar IV Course At Universitas PGRI Wiranegara. - Barotun Mabaroh; Dewi Ani Sartika; Rasyidah Nur Aisyah (Institut Agama Islam Negeri (IAIN) Manado, 2021)
This study was conducted for discovering the students’ preference of learning Grammar using TOEFL Applications; 1) NST TOEFL Explorer and 2) Genius TOEFL. This research was important in order to evaluate the effective media for learning grammar TOEFL. The researchers used descriptive research which was conducted on 29th March 2019 until 28th May 2019. The subject of this study was the students’ who joined in ICT-Based learning of Grammar IV Course at Universitas PGRI Wiranegara Pasuruan. To get the data, the researchers used some instruments. Those were observation, questionnaire, interview, and documentation. The finding from the questionnaire showed that there were 32% of students class A had choosen NST TOEFL Explorer application, but 68% of them had preferred using Genius TOEFL application. There were 17% of students class B choosen NST TOEFL Explorer application and 83% of students class B had preferred using Genius TOEFL application. From this percentage, it can be shown that Genius TOEFL was more preferred to use for Grammar IV Course in Universitas PGRI Wiranegara Pasuruan. It was also found that the students average score after using NST TOEFL application was 20, whereas they got 65 by using Genius TOEFL. This result did not claim that Genius TOEFL was better than NST TOEFL explorer, but this contributed how an application could enhance the students’ interest in using it for learnig and support their achievement. Future researchers are suggested to justify this research result to formulate best criteria of effective ICT-based media.Keywords: ICT, learning Media, NST TOEFL Explorer, Genius TOEFL, Students’ Preference.